EDIBLE OFFAL CHICKEN SUPERIOR TO BALITNAK (KUB) WHICH IS GIVEN TURMERIC EXTRACT THROUGH DRINKING WATER - S.A., Sriningsih; Siti, N.W.; Wibawa, A.A.P.P. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the Edible Offal of Balitnak Superior Village Chicken (KUB) Given Turmeric Extract Through Drinking Water. This research was conducted at the Sesetan Teaching Farm, Udayana Faculty of Animal Husbandry, for 8 weeks from January to March 2023 using a completely randomized design (CRD) consisting of 4 treatment and 5 replication, so there were 20 experimental units. Each unit contains 2 birds that are 10 days old and a total of 40 birds. The treatment consisted of P0 (commercial ration of CP 511B without turmeric ectract in drinking water), P1 (commercial ration of CP 511B and administration of 1% turmeric in drinking water), P2 (commercial ration of CP 511B and administration of 2% turmeric extract in drinking water), P3 (commercial ration of CP 511B an administration of 3% turmeric extract in drinking water). The variables observed were percentage of head, percentage of legs, percentage heart, percentage of liver, length of small intetine, percentage og proventriculus, and percentage of ventricles. The results of this study indicate that the percentage of P0 treated ventricles. P1, and P3 were significantly different (P<0,05) higher than the P2 treatmen, then the percentage of head, legs, heart, liver, small intestune lenght, and the percentage of proventriculus produced no significant difference (P>0,05) compared to the P0 treatment. Above it can be concluded that giving turmeric extract through drinking water up to a level of 3% in KUB chickens can improve the percentage of ventricles, but gives result that do not affect the percentage of head, legs, heart, liver, length of small intestine, and percentage of proventriculus.